Blood ethylene oxide, systemic inflammation, and serum lipid profiles: Results from NHANES 2013–2016. (July 2022) - Zhu, Xu; Kong, Xiangying; Chen, Mengli; Shi, Shi; Cheang, Iokfai; Zhu, Qingqing; Lu, Xinyi; Yue, Xin; Tang, Yuan; Liao, Shengen; Zhou, Yanli; Zhang, Haifeng; et al.
Abstract: Background: Using data from the National Health and Nutrition Examination Survey (NHANES), this study aimed to explore the relationship between ethylene oxide (EO) exposure and serum lipid profiles as well as the mediation effect of systemic inflammation among the general adult population. Methods: This cross-sectional study analyzed NHANES data from 2013 to 2016, examining a total of 2721 participants. The EO biomarker (hemoglobin adduct of EO [HbEO]) was quantified in blood using a high-performance liquid chromatography-tandem mass spectrometry (HPLC–MS/MS) method. The association among HbEO levels, inflammatory biomarkers, and four serum lipids was evaluated using a multivariable linear regression model. Mediating analysis was performed to examine the effect of inflammatory biomarkers on the relationship between HbEO levels and serum lipid profiles. Results: As the quartiles of HbEO increased, high-density lipoprotein cholesterol (HDL-C) monotonically decreased ( p for trend <0.001). Using the lowest quartile of HbEO as a reference, the percent change for HDL-C was 6.30% (95% CI: 3.89%, 8.71%) in the highest quartile of HbEO. HbEO levels were dose-dependently associated with triglycerides (TG) ( p for trend = 0.001). The percent change in TG in the fourth quartile of HbEO was 17.24% (95% CI: 2.01%, 32.48%) compared to the first quartile. Overall, inflammatory biomarkers (hs-CRP, alkaline phosphatase, white blood cell count, neutrophil count, and lymphocyte count) increased monotonically in correlation with increasing HbEO levels (all p for trend <0.01); were positively correlated with total cholesterol (TC), TG, and low-density lipoprotein cholesterol (LDL-C); and were negatively associated with HDL-C. Additionally, inflammatory biomarkers strongly mediated the relationships between HbEO and HDL-C and TG with maximum mediated proportions of 21.40% and 33.40%, respectively. Conclusions: These findings suggest that HbEO is closely linked to serum lipid profiles and that systemic inflammation may be a key mediator of this association. Graphical abstract: Image 1 Highlights: Hemoglobin adduct of ethylene oxide (HbEO) is linearly and negatively associated with HDL-C. HbEO is linearly and positively associated with TG. Systemic inflammation partly mediates the associations between HbEO and serum lipid.